Personal Hygiene pada Pedagang Makanan Siap Saji di Desa Latta Kecamatan Teluk Ambon Baguala - Rusdin Waily (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Personal hygiene plays a significant role in food contamination, influenced by several factors including the cleanliness of eating utensils. The human body can be a source of contamination, especially when hygiene is not maintained properly, leading to the contamination of food and utensils. Contamination is not only derived from food and water sources but also from unsanitary eating equipment. In Indonesia, regulations have been established under the Minister of Health Regulation No. 1096/Menkes/SK/VI/2011 concerning hygiene and sanitation requirements for food service providers. This study aims to assess the personal hygiene of ready-to-eat food handlers in Latta Village, Teluk Ambon Baguala District. The research is descriptive in nature, using interviews and observations. The study population consisted of 22 ready-to-eat food vendors, with a sample of 5 vendors selected. The results showed that all five food handlers (Vendors I to V) did not meet the hygiene requirements according to the Ministry of Health Regulation No. 1096/Menkes/Per/VI/2011, with a contamination level of 0 CFU. This indicates that the personal hygiene of the five food handlers in Latta Village, Teluk Ambon Baguala District, does not meet the required standards.